Where Olive Branches Weep: Palestine’s Lost Generation : Where Olive Branches Weep: The Plight of Health Crisis and Tumult Surrounding the Crisis in Gaza - Ramadhany, Ghifarie Aulia; Fany, Alfa Sofia; Fikry, Zahira Farasya; Manullang , Abel Josafat (Universitas Nahdlatul Ulama Surabaya, 2025)
This paper seeks to understand the worsening health crisis in Gaza, which affects both the people and the healthcare infrastructure, as well as the regional and international responses to this plight. Gaza has become a stage for a humanitarian crisis as a result of Israeli incursions into Palestine. Among the multifaceted crises occurring in Gaza, the healthcare sector has borne the brunt of the impact. The authors employ qualitative research with a descriptive method to examine the problem at hand. The article begins by discussing the health crisis in Gaza, which has worsened following the Israeli attacks after October 7. It highlights the reported assaults on healthcare infrastructure and medical workers that have further strained the existing medical capacity. Considering recent developments, it can be observed that regional states in the Middle East and the international community have not remained idle amid the ongoing crisis in Gaza. Various efforts have been made to address the crisis, involving both state and non-state actors, with aims ranging from calls for boycotts, recognition of Palestine as a state, to the issuance of arrest warrants against Israeli leaders. Overall, this paper concludes that despite the worsening health crisis in Gaza, recent developments indicate active efforts from the international community to alleviate the suffering.